The Anticonvulsant Effects of Different Cannabis Extracts in a Zebrafish Model of Epilepsy - Karen Jackson; Maytal Shabat-Simon; Jonathan Bar-On; Rafi Steckler; Soliman Khatib; Snait Tamir; Paula Adriana Pitashny (Biomolecules)
Epilepsy is a widespread neurological disorder that remains a critical global public health challenge. While numerous antiepileptic drugs (AEDs) are available, many patients either fail to achieve adequate seizure control or experience significant side effects. One promising alternative is pure cannabidiol (CBD), but using a whole cannabis extract may be equally effective and preferred for some patients. In the current study, we employed the pentylenetetrazole (PTZ)-induced hyperactivity model in zebrafish to compare the effects of CBD with various cannabis extracts. We evaluated three cannabis strains, each subjected to three different extraction methods, and benchmarked the results against the commercially available AED valproic acid (VPA). Our findings revealed that 5.7 µg/mL of CBD and 10 µg/mL of different extracts significantly reduced movement compared to PTZ and VPA. In addition, effective extracts produced effects similar to pure CBD despite containing much lower molecule levels. These results reinforced and expanded previous evidence supporting the clinical potential of both CBD and whole cannabis extracts for seizure control while suggesting a possible entourage effect. Further research is necessary to determine which patients may benefit more from pure CBD versus those who might prefer whole cannabis extracts.